دراسة خطر الانجراف المائي لترب حوض سد 16 تشرين في محافظة اللاذقية باستخدام تقنيات نظم المعلومات الجغرافية GIS - بركات, منى; محفوض, ايلين; كويس, أيمن عبد اللطيف (Latakia University Journal -Biological Sciences Series, 2013)
يعد الانجراف المائي للتربة من أبرز المشاكل البيئية التي تتعرض لها ترب الساحل السوري وخصوصا الترب المحيطة بالمستجمعات المائية في محافظة اللاذقية. وتتأثر شدة الانجراف بكل من خواص التربة, درجة الميل, الغطاء النباتي والشدة المطرية ..الخ اجريت الدراسة في منطقة حوض سد 16 تشرين بهدف إنشاء خريطة خطر الانجراف المائي لحوض السد من اجل تحديد درجة خطورة الانجراف المائي للمناطق الواقعة ضمن نطاق التأثير في حوض السد وتصنيفها بالاعتماد على نموذج كورين. تم تحديد صفوف كل من ( قوام التربة, النسبة المئوية للحصى, عمق التربة ) لحساب دليل قابلية التربة للانجراف, وتم إعداد خريطة لعامل قابلية التربة للانجراف باستخدام برنامجArcGIS 10 وحددت صفوف كل من درجة الميل وعامل الحت المطري وتم دمجها بصفوف عامل قابلية التربة للانجراف ورسمت خريطة خطر الانجراف المحتمل. أنشئت خريطة خطر الانجراف الفعلي بعد تحديد صفوف الغطاء النباتي ودمجها بصفوف خطر الانجراف المحتمل, حيث بلغت(33.87,46.15,33.63 ) للصفوف منخفض, متوسط وشديد على التوالي من المساحة المدروسة. كما أظهرت النتائج أن استخدام نموذج CORINE وتقنيات نظم المعلومات الجغرافية وبرامج الحاسوب ArcGISوسيلة فعالة في دراسة خطر الانجراف فهي تمكننا من إنشاء خريطة لخطر الانجراف المائي للتربة بشكل سريع وبكلفة أقل. Soil water erosion is the most prominent environmental risk facing Syrian costal soils, especially from locations surrounding water basin. The severity of soil water erosion is greatly influenced by soil properties, slope, climate, and vegetation and Rainfall intensity. This study aims to establish a risk map for soil water erosion in the Sixteen Tishreen basin area in the province of Lattakia to determine and classify the degree of risk for soil water erosion for locations in the study area according to Coordination of Information on the Environment (CORINE) Model. Collected samples were located using GIS technique and data regarding soil texture, slope and soil depth were classified to calculate the viability for soil erosion. A map for the Erodibility of soil erosion was then established using ArcGIS 10 on which grouped degree of slopes and Erosivity index were superimposed, along with class of soil Erodibility index, in order to establish a map for soil erosion risk. The actual soil erosion risk map was then established as a result of incorporating grouped vegetation covers with grouped potential erosion risks. Values for actual soil erosion risks were 33.87, 46.15, and 33.63 for low, intermediate and high, respectively in the studied area. It can be concluded that using CORINE model, GIS technique and ArcGIS software is an effective tool to investigate and establish a map that determines the risk for soil water erosion quickly with minimum cost.